The Psychological Capital of Workers and Professional Wellbeing. The Moderating Role of Work Mode - Zwardoń-Kuchciak, Olga; Hauk, Mateusz (Przegląd Psychologiczny, 2025)
Aim: In times of increasingly dynamic change, the responsibility for ensuring the professional wellbeing of employees has fallen to the employer, and organizations are systematically looking for ways to take care of their employees. The question of which factors influence the formation of occupational well-being, especially in the context of work mode, is extremely relevant to the functioning of modern organizations. Methods: The study used the Occupational Wellbeing Questionnaire, which allows a subjective self-assessment of one’s work and its environment. In addition, psychological capital and its components were evaluated with the Psychological Capital Questionnaire. Work mode was determined using a closed question included in the survey. The study included a total of 162 people (111 women and 51 men), aged 21 to 55 (M = 35, SD = 7.63). Results: A positive relationship was observed between psychological capital and occupational wellbeing, with work mode having varying effects on occupational wellbeing. In addition, remote and hybrid working had significant indirect moderating effects on the relationship between psychological capital and professional wellbeing. Conclusion: The relationships between psychological capital, professional wellbeing and work mode require further study. Nevertheless, our findings indicate directions for preparing development and support activities aimed at maintaining or increasing wellbeing and the effect of work mode; as such they have important practical implications for employers, HR departments and managers.